Natural Language Processing using R Pocket Primer - Campesato, Oswald; Campesato, Oswald (Mercury Learning and Information, 2022)
This book is for developers who are looking for an overview of basic concepts in Natural Language Processing using R. It casts a wide net of techniques to help developers who have a range of technical backgrounds. Numerous code samples and listings are included to support myriad topics. The final chapter presents the Transformer Architecture, BERT-based models, and the GPT family of models, all of which were developed during the past three years. Companion files with source code and figures are included and available for downloading by emailing the publisher at info@merclearning.com with proof of purchase.FEATURES:Covers extensive topics related to natural language processing using RFeatures companion files with source code and figures from the book